Investigating the Effect of Oral Administration of Zinc Sulfate on Some Acute Phase Proteins of Serum Antioxidants and Thyroid Hormones in Women with Diabetes Type ΙΙ and Comparing it with Animal Model (Rat) - Alireza Mehdizadeh (Journal of Global Pharma Technology, 2017)
Introduction Diabetes is a non-communicable disease that is very common and costly and it has been known as one of the major causes of death in the world, manifested in the form of gradual increase in blood glucose concentration and reduced blood content or disorder in insulin signaling pathway. In this regard, many researchers concluded that minerals play a significant role in controlling blood sugar and improving the general state of diabetic patients. Therefore, the effect of oral administration of zinc as a micronutrient that has the insulin-like properties and involved in the production, storage, and secretion of insulin with different doses was studied in both human and animal models (rats).Methodology Human study includes four groups, in which one group was positive control group and three other groups received 25, 12.5, and 50 mg zinc on daily basis, and animal study included five groups including positive control group, negative control group, and three groups received 25, 12.5, and 50 mg zinc per kg of food. It should be stated that to create diabetes in rats, Streptozotocin drug with dose of 45 kg/mg and citrate buffer solvent injected in the form of IP were used. Results In a recent study, we concluded that study groups received different doses of zinc showed significant difference with control groups in both human and animal models, in other measured parameters such as acute phase proteins like CRP, total antioxidant capacity (TAC), malondialdehyde (MDA), and FT3 thyroid hormone FT3 in addition to the blood glucose reduction. Generally, it can be concluded that by taking zinc, acute phase protein reduced in these patients and by strengthening the body immune system through increasing the antioxidant capacity, it leads to reduced malondialdehyde.Keywords: Diabetes disease, Human and rat, Acute phase protein, Total antioxidant capacity, Malondialdehyde. Thyroid hormone FT3- blood glucose.